Application of Linear Programming Approach for Determining Optimum Production Cost - Bala, Shujit Kumar; Bala, Nandita Rani; Biswas, Hena Rani; Mondal, Surajit Kumar (Asian Business Review, 2020)
Cost optimization problem deals with that problem which aims to find out the most appropriate ways to fulfill the demand of a particular product of any manufacturing company with minimum cost. Linear programming is one of the most appropriate techniques for scheduling the optimum cost of manufacturing. In this study, the production schedule of a bicycle manufacturing company is taken into account. The mathematical formulation of the problem under consideration is performed by using a linear programming approach. An operations research software, TORA (Temporary-Ordered Routing Algorithm), has been used in solving the problem and analyzing the results. Results reveal that a specific schedule has a great impact on optimizing the production cost.